Intestinal response to salinity challenge in the Senegalese sole (Solea senegalensis) - Ruiz-Jarabo, I. (2019)
Fish are continuously forced to actively absorb or expel water and ions through epithelia. Most studies have focused on the gill due to its role in Na+ and Cl- trafficking. However, comparatively few studies have focused on the changing function of the intestine in response to external salinity. Therefore, the present study investigated the main intestinal changes of long-term acclimation of the Senegalese sole (Solea senegalensis) to 5,15, 38 and 55 ppt. Through the measurement of short-circuit current (Isc) in Ussing chambers and biochemical approaches, we described a clear anterior/posterior functional regionalization of the intestine in response to salinity. The use of specific inhibitors in Ussing chamber experiments, revealed that the bumetanide-sensitive Na+/K+/Cl- co-transporters are the main effectors of Cl- uptake in both anterior intestine and rectum. Additionally, the use of the anion exchanger specific inhibitor, DIDS, showed a salinity/region dependency of anion exchanger function. Moreover, we also described ouabain-sensitive Na+/K+-ATPase (NKA) and Bafilomycin Al-sensitive H-ATPase activities (HA), which displayed changes related to salinity and intestinal region. However, the most striking result of the present study is the description of an omeprazole-sensitive H+/K+-ATPase (HKA) in the rectum of Senegalese sole. Its activity was consistently measurable and increased at lower salinities, reaching rates even higher than those of the NKA. Together our results provide new insights into the changing role of the intestine in response to external salinity in teleost fish. The rectal activity of HKA offers an alternative/cooperative mechanism with the HA in the final processing of intestinal water absorption by apical titration of secreted bicarbonate. (C) 2016 Elsevier Inc. All rights reserved.